Nutraceuticals and Functional Foods: Bridging Health and Food under a New Perspective - Santini, Antonello (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, entitled "Nutraceuticals and Functional Foods: Bridging Health and Food Under a New Perspective", aims to approach the current state-of-the-art research on nutraceuticals and functional foods. The main issue in this field of research is the sustainability and recovery of bioactive substances from vegetal- or animal-origin byproducts to project and realize novel food supplements and nutraceuticals. Low environmental impact, safety, new food sources and analytical methodologies are of growing interest in the research area of food. The perspective approach addresses the mechanism of action of nutraceuticals, safety and functional foods and nutraceuticals' mechanisms of action, revealing new possibilities for their use as tools in a complementary proactive approach to certain health issues to prevent the onset of health conditions or to be used in subjects who do not qualify for a conventional therapeutical approach. The areas involved in this perspective range from food chemistry and analysis to nutrition and from safety to sustainability; new therapeutical approaches and novel techniques of analysis and formulation are also involved, which require a wide inter- and multi-disciplinary approach. The overall assessment of these aspects creates new challenges for research and also impacts sustainability, health and safety. This Special Issue may also consider the bridging of health and food in their different declinations from a new perspective.